Pemetaan riset teori agensi: Bibliometrik analisis berbasis data Scopus - Nuansari, Shindy Dwita; Ratri, Indira Nuansa (Implementasi Manajemen & Kewirausahaan, 2022)
Agency theory provides a direction regarding agency in organizations. The emergence of this theory provides meaningful guidance in an organization in overcoming agency problems that occur due to conflicts of interest between principles and agents. Agency theory is an old theory in accounting and financial management, but its existence is very much needed today. This article aims to present the existence and development of the application of agency theory in various types of research, as well as to prove the strength of this theory based on support from various documents. This research was conducted by adopting a bibliometric analysis based on the Scopus database. Based on the keywords used, namely related to agency theory, this study succeeded in obtaining 564 documents for further analysis. This study reports the results using standard bibliometric indicators such as year of publication, document type, source type, source title, subject language, keyword analysis, article author, and active institution. Based on our findings, the existence of research that adopts agency theory is still highly recognized with evidence of an increasing trend of growth every year since our observation period, namely from 2013-2020, but there has been a slight decline in 2021. Research that adopts agency theory has now penetrated into various fields such as engineering, psychology, and so forth.